KOMPOSISI GAMELAN KELOMPOK SARDULO ANUROGO PADA FESTIVAL REYOG NASIONAL 2019 - Sigit Setiawan; Anggono Kusumo Wibowo (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2023)
This research reveals the composition of the Reyog Ponorogo gamelan, a case study of the Reyog Sardulo Anurogo group in Jember, East Java, in the context of the 2019 National Reyog Festival. The reason for selecting Sardulo Anurogo as the case study subject is due to the group's interesting pluralism aspect, where Reyog is not only studied by the Javanese Ponoragan ethnic group, but also by other ethnic groups in Jember, Madura. The 2019 National Reyog Festival also marked a significant moment for Sardulo Anurogo, as they achieved a top 3 position in the festival, representing the group's highest achievement. The approach used is based on the ideas of I Wayan Sadra, who proposed four methods for composing music. These are (1) the principle of growth, (2) sound transformation or medium, and (3) range or tonal area. These principles areapplied to analyze the composition of the Reyog Sardulo Anurogo gamelan. The research result is the categorization of Reyog music development methods, which can be used as a prototype for composing and enhancing the creative aspects of Reyog gamelan.